The Equity Research Program’s Effect on Technology Investors: The Tel-Aviv Stock Exchange Case Study - Rothman, Tiran; Yakar, Chen (European Scientific Journal, ESJ, 2019)
The Tel-Aviv Stock Exchange (TASE) initiated an equity research program in 2016 dedicated to the technology sector. The main goal of the program was to draw more investor attention to Israeli tech firms. Today, nearly all equity research is performed by stock brokers, investment banks, and other entities which have a financial interest in the market. On the other hand, independent equity research is a boutique service offered by only a few firms worldwide. The aim of such research is to provide an unbiased opinion on the state of a company, including its share price and potential forthcoming changes. We conducted a study to explore events, such as initiation analysis report publications, as the release of new information to market participants. We hope to contribute to the growing literature on the effect of analyst reports on investor activities. Our findings indicate a broad market reaction to equity research reports published in TASE during 2017-2018.